GRI Index 2021 - World Bank (World Bank, Washington, DC, 2021)
This 2021 World Bank GRI Index is an inventory of the sustainability considerations used in World Bank (Bank) lending and analytical services as well as its corporate practices. This sustainability disclosure index has been prepared in accordance with the Core option of the GRI Standards. The GRI Index covers activities carried out during fiscal 2021, from July 1, 2020, to June 30, 2021. The Coronavirus (COVID-19) pandemic has impacted the Bank’s operations and staff activities through reduced travel, an extended shutdown of its offices, and a shift in staff health services. Where significant, these impacts have been noted in the report.